Determinant of Intention to Use Sharia Fintech Among Generation Z - Akhmad Nur Zaroni; Norvadewi; Septiani (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
Generation Z (Gen Z) is the largest community in Indonesia. Generation Z actively uses the Internet and social media. The Internet has changed their financial behavior to be cashless and consumptive, mainly supported by the development of Fintech with various financial products and services that facilitate various transactions, investments, and fund distribution. Along with the development of the Islamic economy, Sharia fintech is also multiplying. This study aims to identify factors influencing the intention to use Sharia Fintech among generation Z in Samarinda. This study is a quantitative study with 94 respondents. Use multiple regression analysis with SPSS version 25. The results showed that knowledge and perceived ease of use influenced the intention to use Sharia Fintech. In contrast, the perceived trust did not affect the intention to use Sharia fintech in generation Z. Determination coefficient (R2) test results showed that knowledge, perceived ease of use, and perceived trust had an effect of 41.6% on the interest in using Sharia fintech in generation Z.